A nationwide analysis of re-exploration after liver transplant. Issue 3 (March 2018) - Moghadamyeghaneh, Zhobin; Alameddine, Mahmoud; Jue, Joshua S.; Guerra, Giselle; Selvaggi, Gennaro; Nishida, Seigo; Fan, J.; Beduschi, Thiago; Vianna, Rodrigo
Abstract: Background: A retrospective review to investigate rate and outcomes of re-exploration following liver transplantation in the United States. Methods: The NIS database was used to examine outcomes of patients who underwent re-exploration following liver transplantation from 2002 to 2012. Multivariate regression analysis was performed to compare outcomes of patients with and without reoperation. Results: We sampled a total of 12, 075 patients who underwent liver transplantation. Of these, 1505 (12.5%) had re-exploration during the same hospitalization. Hemorrhagic (67.9%) and biliary tract anastomosis complication (14.8%) were the most common reasons for reoperation. Patients with reoperation had a significantly higher mortality than those who did not (11.6% vs. 3.8%, AOR: 3.01, P  < 0.01). Preoperative coagulopathy (AOR: 1.71, P  < 0.01) and renal failure (AOR: 1.57, P  < 0.01) were associated with hemorrhagic complications. Peripheral vascular disorders (AOR: 2.15, P  < 0.01) and coagulopathy (AOR: 1.32, P  < 0.01) were significantly associated with vascular complications. Risk of wound disruption was significantly higher in patients with chronic pulmonary disease (AOR: 1.50, P  < 0.01). Conclusion: Re-exploration after liver transplantation is relatively common (12.5%), with hemorrhagic complication as the most common reason for reoperation. Preoperative coagulation disorders significantly increase hemorrhagic and vascular complications. Further clinical trails should investigate prophylactic strategies in high risk patients to prevent unplanned reoperation.